2019
DOI: 10.1186/s13017-019-0277-7
|View full text |Cite
|
Sign up to set email alerts
|

New hemostatic device for grade IV–V liver injury in porcine model: a proof of concept

Abstract: BackgroundThe liver is the most injured organ following abdominal trauma. Uncontrolled bleeding remains the main cause of early liver injury-related death, with a mortality rate of 50–54% in the first 24 h after admission and with 80% of operative deaths. Packing and reoperation account for the increased survival in severe liver trauma, and they are recommended for severe liver injuries (grades IV–V).Perihepatic packing can lead to several potential complications. An excessive packing can cause complications d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It was also aimed that the liver hemorrhage that is checked about 48-72 hours after the placement of compresses has stopped, otherwise it has the potential to have quite complex results, but if excessive packaging is involved due to surgical experience, it may cause complications again. [23] In the other study comparing surgical hemostatic sponges in liver injuries by using the rat model, three different types of sponges were applied as gelatin, horse collagen and oxidized cellulose, and their hemostatic capacities were compared. [24] Fontes et al observed that the similar hemostatic effects in all groups however, the gelatin sponge showed more inflammation and adhesion to the structures adjacent to the procedure than other groups.…”
Section: Discussionmentioning
confidence: 99%
“…It was also aimed that the liver hemorrhage that is checked about 48-72 hours after the placement of compresses has stopped, otherwise it has the potential to have quite complex results, but if excessive packaging is involved due to surgical experience, it may cause complications again. [23] In the other study comparing surgical hemostatic sponges in liver injuries by using the rat model, three different types of sponges were applied as gelatin, horse collagen and oxidized cellulose, and their hemostatic capacities were compared. [24] Fontes et al observed that the similar hemostatic effects in all groups however, the gelatin sponge showed more inflammation and adhesion to the structures adjacent to the procedure than other groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat liver laceration model, intravenous injection of HAPPI results in a significant decrease in blood loss from 19.0 g/kg (in the saline group) to 14.9 g/kg ( p = 0.0070) with a mortality rate decrease from 50% to 12.5% within the 2‐h monitoring period after injury. This nonsurgical hemostasis strategy for fatal hepatic hemorrhage is of clinical significance, given that liver is one of the most frequently injured organs in abdominal trauma, 46,47 and uncontrolled hemorrhage is the key cause of liver injury‐related casualty with a mortality rate up to 80% 48,49 . In case of bleeding episodes from hemophilia A mice, compared to the saline group, HAPPI‐treated mice showed much slower bleeding and three‐fold less blood loss with the 20‐min monitoring period, presumably due to the enhanced primary hemostasis step.…”
Section: Discussionmentioning
confidence: 99%
“…Many methods have been tried to prevent liver parenchymal bleeding depending on the cause of the bleeding. Among these methods, there are also the use of hemostatic materials [12][13][14] . There are studies on hemostats in normal bleeding, but there was no study with hemostats on intraabdominal solid organ bleeding in heparinized patients.…”
Section: Discussionmentioning
confidence: 99%